Process Intensification in Pneumatically Agitated Slurry Reactors. (March 2021) - Geng, Shujun; Mao, Zai-Sha; Huang, Qingshan; Yang, Chao
Abstract: Pneumatically agitated slurry reactors, including bubble column reactors and airlift loop reactors (ALRs), are important gas–liquid–solid multiphase reactors. These reactors have been widely applied in many processes, especially in the biological fermentation and energy chemical industry, due to their low shear stress, good mixing, perfect mass-/heat-transfer properties, and relatively low costs. To further improve the performance of slurry reactors (i.e., mixing and mass/heat transfer) and to satisfy industrial requirements (e.g., temperature control, reduction of back-mixing, and product separation), the process intensification of slurry reactors is essential. This article starts by reviewing the latest advancements in the intensification of mixing and mass/heat transfer in these two types of reactors. It then summarizes process-intensification methods for mixing and separation that allow continuous production in these slurry reactors. Process-intensification technology that integrates directional flow in an ALR with simple solid–liquid separation in a hydrocyclone is recommended for its high efficiency and low costs. This article also systematically addresses vital considerations and challenges, including flow regime discrimination, gas spargers, solid particle effects, and other concerns in slurry reactors. It introduces the progress of numerical simulation using computational fluid dynamics (CFD) for the rational design of slurry reactors and discusses difficulties in modeling. Finally, it presents conclusions and perspectives on the design of industrial slurry reactors.